Lecturer Professionalism in Research and Community Service - Waska Warta; Haura Karlina; Zakia Hary Nisa (Yayasan Letiges Konsultan Sosial, 2024)
A robust Quality Assurance System (QAS) is essential to ensure consistent quality in higher education, encompassing internal and external measures. This study examines the QAS at STIKes Bhakti Pertiwi Indonesia (BPI), focusing on its application in enhancing lecturer professionalism in research and community service. This study uses a qualitative approach to the case study type. Data collection is done through interviews, observations, and documentation. Data analysis is done by reducing, displaying, and verifying data. The findings show that implementing internal and external quality assurance systems in all academic areas, including education, research, and community service, is essential. Effective implementation of the Tridharma of higher education, which consists of these three pillars, reflects the professionalism of lecturers. The quality assurance system operates through the PPEPP (Penetapan, Pelaksanaan, Evaluasi, Pengendalian, dan Peningkatan) activity cycle, which includes monitoring and evaluation, internal quality audits, satisfaction surveys, and accreditation results. The study highlights the annual update of the biannual standards for research and community service lecturers, underscoring the dynamic nature of quality assurance in higher education.